Climate change and Singapore - Ng, Gwendolyn Ling Kuan. (2011)
The Arctic is a region located at the Northern Hemisphere, accounting for about 6 percent of the Earth’s total surface area. The Arctic which was covered in ice caps and glaciers was once impenetrable by humans. At present, ships are able to pass through this region for a period of 3 to 4 weeks. This phenomenon is caused by climate change, resulting from the increasing release of Greenhouse gases into the Earth’s atmosphere which accelerated the melting of Arctic’s ice caps and glaciers.This led to the opening of the Arctic sea routes and a more accessible Arctic region. Although there are no official routes through the Arctic as ice is constantly changing in pattern, explorers have found three main Arctic passages namely the Northeast Passage also known as the Northern Sea Route (NSR), Northwest Passage (NWP) and the Central Arctic Ocean Route. Commercial shipping is benefitting from the shorter distances of these routes as compared to the traditional Suez Canal Route.